FEATURE HISTOGENETIC PROCESSES OF CONDUCTING CARDIOMYOCYTES OF THE HUMAN EMBRYONIC HEART - Silkina, Yu.V.; Chmel, S.I.; Kozlova, Yu.V. (World of Medicine and Biology, 2013)
We exploed the heart of human embryos and fetuses since 4th to 12th week of development. Used immunohistochemical and lektinohistochemical methods using a monoclonal antibody: NF, α-SMA, MSA and lectins: PNA, WGA, HPA. We found that the early myocytes are pluripotent. Bundle of His developed from actively migrating cells. Continues Purkinje’s fibers differentiation is after 12th weeks of prenatal development and before this period it not have the mature structure. We also established that before the final formation of the bundle of His area, that connects the atrial and ventricular myocardial portion, is the ventricular myocardium and it takes role of early conduction system. The formation of the sinoatrial and atrioventricular nodes is by recruiting of multipotent cardiomyocytes, but is not the result migration of neural crest cells or epicardium cells. The conductive system cells coexpression the neuronal and myofibrillar proteins and alpha-smooth muscle actin. Most migratory activity have the bundle of His and his branch. Distal conduction system in the atria and ventricles to 12th week of development do not have a specific location and histological structure. The conduction system cells and contractile myosytes in human embryonic heart are different only immunohistochemical characteristics.